2021
DOI: 10.1155/2021/6381549
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Seepage Characteristics of Fractured Rock Mass under Different Stress Conditions

Abstract: In order to obtain the mechanical behavior and permeability characteristics of coal under the coupling action of stress and seepage, permeability tests under different confining pressures in the process of deformation and destruction of briquette coal were carried out using the electrohydraulic servo system of rock mechanics. The stress-strain and permeability evolution curves of briquette coal during the whole deformation process were obtained. The mechanical behavior and permeability coefficient evolution re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The surface water source and some spring points may dry up during water flushing accidents in the construction phase. Studies to date, therefore, have shown that underground engineering construction can have serious effects on the groundwater environment and the supply of groundwater resources [10,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The surface water source and some spring points may dry up during water flushing accidents in the construction phase. Studies to date, therefore, have shown that underground engineering construction can have serious effects on the groundwater environment and the supply of groundwater resources [10,23,24].…”
Section: Introductionmentioning
confidence: 99%